Multi-agent toolbox for fault tolerant networked control systems design - Costa, José Sá da (2019)
The design of fault tolerant control (FTC) systems of large-scale complex networked control systems (NCS) is a difficult task due to the large number of sensors and actuators spatially distributed and networked connected. Despite the research effort on developing FTC systems most of these developments are designed globally leading to centralized FTC solutions inadequate to NCS. In this paper we present the first version of a toolbox based on multi-agent systems (MAS) to design FTC systems for complex NCS. This toolbox is based on a decentralized FTC of NCS which relies on causal graph partitioning of the NCS digraph model and on intelligent distributed computing using MAS.